2011
DOI: 10.4067/s0717-97072011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometry Microdetermination of Some Antihypertensive Drugs in Pure Form and in Pharmaceutical Formulations

Abstract: Simple, rapid, accurate, precise and sensitive spectrophotometric method for the microdetermination of enalapril maleate (ENM) and lisinopril dihydrate (LIS) has been developed. The method is based on oxidation of the drug by potassium permanganate in acidic medium and determine the unreacted oxidant by measuring the decrease in absorbance for three different acidic dyes; acid red 73 (AR), amaranth dye [acid red 27] (AM) and acid orange 7 (AO) at a suitable λ max (510, 521 and 484 nm for ENM and 509, 521 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It was observed that complete color development was attained at 40 ± 1°C (7 min) ( Figure 2). The effect of Alizarin concentration on the color development was investigated 3 ml of Alizarin reagent produced maximum color intensity ( Figure 3) [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that complete color development was attained at 40 ± 1°C (7 min) ( Figure 2). The effect of Alizarin concentration on the color development was investigated 3 ml of Alizarin reagent produced maximum color intensity ( Figure 3) [36].…”
Section: Resultsmentioning
confidence: 99%
“…Commercial formulation was successfully analyzed for the lisinopril by the proposed method and the results are compared with reference method (20) (Table 3) did not exceed the theoretical values, which indicates the absence of any difference between the methods compared. The proposed method gives good results for lisinopril in pure and pharmaceutical formulations [35,36]. …”
Section: Stoichiometric Relationshipmentioning
confidence: 95%
“…The literature reveals various analytical methods were described for the determination of LNP such as titrimetric [5,6], Spectrophotometric [7][8][9][10][11][12][13][14][15], spectrofluorometric [16][17][18][19][20], chromatographic [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], derivative UV-spectrophotometric, [39][40] polarography [41][42], radioimmunoassay [43] and fluoroimmunoassay [44].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic importance of Enalapril maleate has led to its increasing use and thus to the development of numerous methods of determining this drug. The determination of the Enalapril maleate, alone or in combination with other drugs, has been carried out by various analytical techniques, such as spectrophotometric methods, which, in most cases, involves extraction with organic solvents [4,5] and many reagents [6][7][8][9], or by high performance liquid chromatography (HPLC), which it is the most common practical technique for the determination of this drug. HPLC methods have the advantage of determining the drug in a much shorter time than other analytical methods, and the degradation products do not interfere [10][11][12].…”
Section: Introductionmentioning
confidence: 99%